(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study was undertaken keeping these conditions in mind. Hence, the examination stress and its effect on children’s personality was systematically measured and compared. In total 120 students were taken different urban area of Bihar. The socio economic statuses of all groups were tried to keep constant. The age of the participants ranged from 12-17 years. The random sampling technique was used to select participants in the study. Descriptive survey method was employed to carry out this piece of research work. Then the Examination stress scale and , Indian Adaptation of Contact Personality Factor Test (Form B) along with personal information sheets were administered in individual settings. The obtained data were analysed with the help of SPSS using various statistical technique like mean, standard deviation (SD), ANOVA, t-test, etc.